2019
DOI: 10.12927/hcq.2019.25913
|View full text |Cite
|
Sign up to set email alerts
|

Rural and Urban Differences in the Risk of Inflammatory Bowel Disease and Subsequent Health Services Utilization in Ontario

Abstract: Canada has one of the highest rates of inflammatory bowel disease (IBD) in the world, with 1 in 140 Canadians currently living with the disease. IBD occurs less often among individuals living in rural households. This protective effect is particularly pronounced in young children, and early-life exposure to the rural environment greatly reduces the risk. However, individuals living in rural areas who have IBD have decreased access to specialist gastroenterology care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…IBD is a disease that occurs most frequently in countries with high socio-economic development, with incidence and prevalence particularly high in Europe and North America [4][5][6][7]. Within Western countries, people in urban areas are more prone to IBD compared to those in rural areas, and this is probably due to differences in lifestyle, resulting in greater exposure to IBD risk factors [8].…”
Section: Introductionmentioning
confidence: 99%
“…IBD is a disease that occurs most frequently in countries with high socio-economic development, with incidence and prevalence particularly high in Europe and North America [4][5][6][7]. Within Western countries, people in urban areas are more prone to IBD compared to those in rural areas, and this is probably due to differences in lifestyle, resulting in greater exposure to IBD risk factors [8].…”
Section: Introductionmentioning
confidence: 99%
“…In a Canadian population study, Kuenzig et al. observed that patients from rural zones were less likely to be treated by a specialist gastroenterologist and presented a higher rate of comorbidities and infectious diseases than patients from urban areas [ 41 ]. Even in a smaller territory like Catalonia, where distances to acute hospital care is in average less than 20 Km [ 42 ], the access to IBD specialists and IBD units differs in rural and urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to suggest a fundamental role of environmental risk factors in the development of the pathology [3]. Within Western countries themselves there is a different incidence between urban and rural areas: the population of the former is in fact more subject to cases of IBDs and this is probably due to the differences in lifestyle, which determine greater exposure to risk factors for CD [4].…”
Section: Introductionmentioning
confidence: 99%